Assessment of immunological, haematological and biochemical status after Sofosbuvir-based combination therapy in HCV Egyptian patients from Menoufia Province - Hany M. Ibrahim, Mohammed A. Soliman, Ibrahim A. El-Elaimy, Rasha S. El-Hageen (Journal of Applied Pharmaceutical Science, 2016)
Chronic hepatitis C virus (HCV) is a serious health problem in Egypt. Although the effectiveness of pegylated interferon (peg-IFN) and ribavirin (RBV) combined therapy, poor response rates and lamentable tolerability were recorded in the chronically HCV infected patients. Sofosbuvir (SOF) target the highly conserved active site of the HCV-specific NS5B polymerase that affect directly the viral replication and has broad genotypic coverage. In the present study we investigated the efficacy of SOF-based combination therapy and its effects on the status of immune cells from chronically infected HCV Egyptian patients. HCV Patients were treated with a combination treatment of SOF, RBV and peg-IFN-α or SOF and RBV for either 12 or 24 weeks. Then biochemical, hematological parameters, immunological phenotyping, PBMCs proliferation and apoptosis were detected pre- and post-treatment. While SOF-based combination therapy improved the liver function, anemia, leucopenia and thrombocytopenia were detected especially after treatment with SOF, RBV and peg-IFN-α-2a.We observed significant reduction in the percentage of CD3+CD4+ and CD3+CD8+ cells post-treatment with either SOF and RBV or SOF, RBV and peg-IFN-α-2a as compared to the baseline. Moreover, SOF-based combination therapy altered the percentage of CD3-CD8+, CD14+ and CD20+ cells. The proliferative capacity of PBMCs was significantly decreased in both regimens, whilst the percentage of apoptotic cells was significantly augmented. SOF-based therapy regimens are efficacious in reducing HCV load in the current study with some adverse effects that include the reduction of the mononuclear cells from the blood periphery by apoptosis.
Keywords: Sofosbuvir therapy, proliferation, apoptosis, monocytes, lymphocytes.